Epicardial Fat Thickness in Children with Classic Congenital Adrenal Hyperplasia - Kotb Abbass Metwalley; Hekma Saad Farghaly; Abdelrahman Abdelhamid (Galenos Yayincilik, 2019)
Objective:Epicardial fat thickness (EFT) is an emerging cardio-metabolic risk factor and has been shown to be related to atherosclerosis. EFT has not been studied in the context of CAH. This study aimed to evaluate EFT in children with CAH and its relation to carotid artery intima-media thickness (CA-IMT) and left ventricular (LV) functions.Methods:Thirty-six children with classical CAH were compared with 36 healthy controls. All patients had confirmed CAH and were receiving steroid substitution therapy. Patients and controls underwent anthropometric evaluation, measurement of fasting lipids, glucose, insulin, homeostasis model assessment for insulin resistance (HOMA-IR). LV functions and EFT were assessed using conventional echocardiography. Duplex ultrasonography was used to measure CA-IMT.Results:Compared to controls, patients had greater EFT (p=0.001), CA-IMT (p=0.01), LV mass index (LVMI) (p=0.001) and prolonged mitral deceleration time (DcT) (p=0.01). CAH patients also had significantly worse HOMA-IR (p=0.001) than controls. Abnormalities were worse in uncontrolled CAH on treatment. Multivariate analysis in CAH subjects showed EFT correlated positively with waist circumference odds ratio (OR) [OR=1.9; 95% confidence interval (CI): 1.07-1.14; p=0.01], 17-hydroxyprogesterone [OR=1.6; 95% CI: 1.33-2.89; p=0.05], testosterone concentration (OR=1.7; 95% CI: 1.55-2.13; p=0.01), LVMI (OR=1.14; 95% Cl: 1.08-1.13; p=0.01), mitral DcT (OR=2.25; 95% CI: 1.15-2.05; p=0.01) and CA-IMT (OR=1.6; 95% CI: 1.15-2.05; p=0.01).Conclusion:EFT is elevated in children with classical CAH, particularly in those with poor control, and is correlated with CA-IMT, LV mass and mitral DcT. Measurement of EFT in CAH children may help to identify those at high risk of developing LV dysfunction and subclinical atherosclerosis.